Personalized Disease Monitoring in Pediatric Onset Multiple Sclerosis Using the Saliva Free Light Chain Test - Ganelin-Cohen, Esther; Tartakovsky, Evgeny; Klepfish, Ely; Golderman, Sizilia; Rozenberg, Ayal; Kaplan, Batia (Frontiers in Immunology, 2022)
Background: Development of new safe methods of monitoring disease activity in the paediatric onset multiple sclerosis (POMS) is a challenging task, especially when trying to refrain from frequent MRI usage. In our recent study, the saliva immunoglobulin free light chains (FLC) were suggested as biomarkers to discriminate between remission and active MS in adults. Objectives: To assess utility of saliva FLC measurements for monitoring disease activity in POMS. Methods: We used semiquantitative Western blot analysis to detect immunoreactive FLC monomers and dimers and to calculate the intensity of their bands. Statistical tests included Firth logistic regression analysis suitable for small sample sizes, and Spearman’s non-parametric correlation. Results: In naïve POMS patients, the saliva levels of FLC in relapse were significantly higher than those in remission. Correlation was found between FLC levels (monomers, dimers or both) and the load of enhanced lesions in MRI scans. FLC levels may be reduced under treatment, especially as result of corticosteroids therapy. Follow-up of individual patients showed the correspondence of changes in the FLC levels to MRI findings. Conclusions: Our results show the potential of the non-invasive saliva FLC test, as a new tool for monitoring the disease activity in POMS.